Is the glass ceiling cracking? A simple test - Ting Hu; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2008)
It has been reported that there is dramatic increase of female workers into manager level jobs during last few decades in the US labor market. Using Standard & Poors Compustat ExecuComp database over 14 years (1992 - 2005), this paper examines whether the glass ceiling in the executive market has been substantially weakened measured by relative compensation by gender and female representation in the top rung of the executive market. Though the status of females in the executive market seems to have been improved, we cannot reject null hypothesis of no change when we test hypotheses whether the glass ceiling has significantly weakened. The results of the hypothesis tests suggest that there is still a long way ahead before gender equality is achieved and the glass ceiling is removed in the executive market.
urn:nbn:de:101:1-20080605130
Keywords: J15; 330; Glass ceiling; executive compensation; gender gap; top rank; hypothesis test; Weibliche Führungskräfte; Erwerbsverlauf; Geschlechterdiskriminierung; Lohndifferenzierung; USA